The Role of Enterprise Intelligence through Social Media Support on SMEs’ Performance in Increasing Sales - Doni Sahputra; Ade Parlaungan Nasution; Siti Lam’ah Nasution (Budapest International Research and Critics University, 2021)
This study aims to analyze the effect of entrepreneurial intelligence through the role of social media on the performance of SMEs in increasing sales. The type of research used is explanatory research with Accidental Sampling technique. The number of samples determined was 80 respondents. Data analysis in this study using SmartPLS version 3.0 software. The results showed that entrepreneurial intelligence consisting of elements of financial intelligence, emotional intelligence, social intelligence and spiritual intelligence had an effect on the performance of SMEs through the role of social media, social media had an effect on performance and sales and performance had an effect on sales.